PENGARUH MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA DI STMIK STIKOM BALI - I Gusti Ngurah Satria Wijaya (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
In teaching and learning activities the role of motivation is very necessary. The low motivation of student learning is often thought to be the cause of the low quality of graduates of a college. This causes in some private universities, learning motivation factors get special attention. Measuring the success of students in following the learning process in an educational institution is indicated by student learning achievement. Based on the background above, the authors conducted a study that aimed to examine the effect of the relationship between student learning motivation on student learning achievement at STIMIK Stikom Bali. The data used in this study are primary data derived from filling out questionnaires from STIMIK Stikom Bali students. The analysis technique used to study the effect of learning motivation on student learning achievement is simple linear regression. The results of this study are student learning motivation has a positive effect on student learning achievement significantly. The benefits of this study can provide evaluation results for the management of STIKOM Bali's STMIK management about the relationship between learning motivation and student learning achievement so that it becomes a consideration for improving the quality of education in STMIK STIKOM Bali.